Protection to breastfeeding in prison space: Integrative Review (Research, Society and Development, 2020)
Breastfeeding is a topic that should be prioritized in prisons and supported by issues related to the physical and psychological conditions of women deprived of liberty, children and their families. The objective was to analyze scientific production in the field of breastfeeding protection in the prison system. This is an integrative review of scientific literature, where the search took place in the following databases: Capes Periodicals, Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval, Scientific Electronic Library Online, Databases of Nursing, SciVerse Scopus the languages ​​used in the research were: English, Portuguese and Spanish, with year of publication from 2013 to 2020. 39 articles were selected, after careful analysis we obtained 09 validated articles. From the interpretative analysis on the theme, the following categories emerged: Protection to breastfeeding within the penal system and Inadequacy to breastfeeding support processes in prison. It is necessary that the penal system adopts well- defined public policies to protect breastfeeding and that there is also greater support for these breastfeeding mothers and their children, as they are women who breastfeed in vulnerable situations, and the global criminal system must protect, support and promote breastfeeding within the prison system.